Kode Etik Guru, Integrasi Dan Profesionalisme Dalam Perspektif Pendidikan Islam - miftahul khairah; Rosdiana (Studia Religia : Jurnal Pemikiran dan Pendidikan Islam, 2026)
This study aims to analyze the factors that influence the formation/strengthening of teacher integrity through professional codes of ethics, including internal, external, regulatory, digital, and spiritual aspects, as well as their implications for teacher integrity and performance in the modern era. The research method used was library research, which involved collecting, evaluating, and analyzing various scientific sources related to the research topic. The analysis was conducted by examining the content of various sources to identify internal, external, regulatory, digital, and spiritual factors that influence teacher integrity. The results of the study indicate that teacher integrity is largely determined by personal moral values, ethical character, commitment to self-development (internal factors), as well as school culture, digital technology, and regulatory oversight (external factors). Consistent application of the code of ethics enhances professionalism, learning quality, and public trust, while violations have the potential to damage the image of the profession. Therefore, continuous strengthening of ethics training, supervision, and digital awareness is necessary.